2022
DOI: 10.1590/1980-5764-dn-2021-0119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of working memory training on cognition in healthy older adults: A systematic review

Abstract: ABSTRACT. The working memory (WM) training in older adults can benefit their cognition. However, there is a dearth of literature reviews on the subject. Objective: This study aimed to investigate and evaluate the effects of WM training on the cognition of healthy older adults, in individual and group interventions reported in the literature. Methods: This is a systematic review involving a qualitative analysis of publications on the SciELO, LILACS, and MEDLINE databases carried out between March and June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
0
2
0
3
Order By: Relevance
“…Revisões de literatura recentes têm observado como os aspectos cognitivos de idosos são impactados pela aposentadoria (Farias et al, 2021); pela prática regular de exercício físico (Vale et al, 2022); pela participação em cursos de inclusão digital (Fujita et al, 2021); por meio de intervenções de treino cognitivo (Silva et al, 2022), entre outros aspectos específicos. Estes estudos apresentam a importância de investigar os aspectos cognitivos relacionados as diferentes esferas da vida, que impactam a cognição como um todo.…”
Section: Dois Estudos Recentes Abordaram Aspectos Diferentes Dos Menc...unclassified
See 1 more Smart Citation
“…Revisões de literatura recentes têm observado como os aspectos cognitivos de idosos são impactados pela aposentadoria (Farias et al, 2021); pela prática regular de exercício físico (Vale et al, 2022); pela participação em cursos de inclusão digital (Fujita et al, 2021); por meio de intervenções de treino cognitivo (Silva et al, 2022), entre outros aspectos específicos. Estes estudos apresentam a importância de investigar os aspectos cognitivos relacionados as diferentes esferas da vida, que impactam a cognição como um todo.…”
Section: Dois Estudos Recentes Abordaram Aspectos Diferentes Dos Menc...unclassified
“…Contrariando estereótipos que associam a idade avançada à redução das capacidades cognitivas, estudos mostram que os idosos possuem uma notável plasticidade cerebral, permitindo a adaptação e assimilação de novas informações (Lima-Silva et al, 2022).…”
Section: Sumário Introduçãounclassified
“…To date, studies have found inconsistent results on the efficacy of WM training in improving cognition in general (see for reviews Teixeira-Santos et al, 2019 ; Saba and Blanchet, 2020 ; Lima-Silva et al, 2022 ) and episodic memory in older people in particular. Regarding episodic memory, some studies have reported improvements ( Schmiedek et al, 2010 ; Richmond et al, 2011 ; Penner et al, 2012 ; Heinzel et al, 2014 ), other studies have not found such improvements ( Dahlin et al, 2008b ; Brehmer et al, 2012 ) and finally, others have obtained improvements in some episodic memory tests but not in others ( Buschkuehl et al, 2008 ; McAvinue et al, 2013 ; Ballesteros et al, 2014 ; Toril et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Memory is one of the most impacted cognitive functions during aging. Aging is accompanied by decline in processing speed, attention span, episodic recall ability and execution of different tasks [3][4][5] . Memory complaints in older individuals are more prevalent among women 6,7 .…”
Section: Introductionmentioning
confidence: 99%